(untitled) (Bangladesh Journal of Animal Science, 2013)
The study was conducted to investigate the socio-economic status of the buffalo farmers and the management practices of buffaloes at different villages of Boraikhali, Hoglabunia and Khawlia union of Morrelgonj upazilla in Bagerhat district of Bangladesh. A total of 60 respondents (20 from each union) were randomly selected from three unions. The data was collected through personal interviewing with pre-tested questioner. The investigation revealed that buffalo rearing was practiced by the middle (30-40 years) and old (>40 years) aged farmers than the young (<30 years). Majority (82%) of the buffalo farmers are educated but only 12% are illiterate. The major occupation of the selected farmers are buffalo rearing (50%) followed by crop production, dairying and poultry rearing. The buffalo farmers basically have no training skills but practiced buffalo rearing as their family profession and 30% of them are influenced by the neighboring buffalo farmers. The buffalo farmers purchased usually one pair of buffalo and reared at least for 2 years. The farmers fed their buffalos with locally available roughages and tree leaves but they did not practice concentrate feeding. The CP contents of the available feedstuffs are comparable and even higher and the CF content was found lower compared to other unconventional feedstuffs indicated the availability of good quality feeds for buffaloes in the studied areas. Semi-intensive feeding system was practiced for rearing buffaloes followed by extensive feeding system. Majority of the buffalo farmers allowed wallowing buffaloes for once or twice in a day for at least 1-2 hours. The major diseases of buffaloes found in the studied areas were foot and mouth followed by black quarter, anthrax and hemorrhagic septicemia. Most of the buffalo farmers practiced vaccination and de-worming regularly. The average cost of one pair of buffalo was 60000-200000 BDT. The annual total cost of production was Tk 5,070, while a gross return was Tk 15,630 per buffalo. The annual food and cloth purchasing capacity of the buffalo farmers were found to be increased to 62.85 and 58.33%, respectively. Similarly, the ability to maintain social status, health care, education and housing of the buffalo farmers were also increased through buffalo rearing. Considering all this parameters related to livelihood, it was clearly found that the socio-economic status of the buffalo farmers was improved through buffalo rearing although the management practices need to be improved with scientific approaches. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18505 Bang. J. Anim. Sci. 2013. 42 (2): 158-164